Rationalising the change in defining non‐viability in the first trimester. Issue 3 (August 2013) - Infante, Fernando; Casikar, Ishwari; Menakaya, Uche; Condous, George
Abstract: Introduction : With the publication of four papers in late 2011, international cut‐offs for definitions of non‐viability in the first trimester of pregnancy were challenged. These definitions were inconsistent across different international guidelines. For example, a gestational sac with absent yolk sac or embryo and a mean diameter of ≥ 16 mm would be classified as a miscarriage in the USA, whereas the same sac would have to measure ≥ 20 mm in the UK or Australia to meet this definition. Likewise, an embryo with no detectable heartbeat and a CRL of ≥ 5 mm would also meet criteria for missed miscarriage in the USA, compared to a CRL ≥ 6 mm in the UK or Australia. Methods : Later in 2011 and then in 2012, guidelines across the three countries were updated and are now consistent, defining an empty gestational sac with a mean diameter of > 25 mm as a non‐viable pregnancy and/or an embryo with CRL > 7 mm and no detectable heartbeat. In this paper we explore the rationale that led to these changes in order to potentially avoid wrongly diagnosing miscarriage at the decision boundary measurements and in turn avoiding inadvertent termination of potentially viable pregnancies. Conclusion : Although reducing women's anxiety and making a definitive diagnosis as early as possible is desirable, the need for absolute certainty is paramount before diagnosis of the death of an early pregnancy is made.